2021
DOI: 10.1037/apl0000875
|View full text |Cite
|
Sign up to set email alerts
|

Excuse me, do you have a minute? An exploration of the dark- and bright-side effects of daily work interruptions for employee well-being.

Abstract: Work intrusions-unexpected interruptions by other people that interrupt ongoing work, bringing it to a temporary halt-are common in today's workplaces. Prior research has focused on the task-based aspect of work intrusions and largely cast intrusions as events that harm employee well-being in general and job satisfaction in particular. We suggest that apart from their task-based aspect, work intrusions also involve a social aspect-interaction with the interrupter-that can have beneficial effects for interrupte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 118 publications
(301 reference statements)
2
41
2
Order By: Relevance
“…For instance, by drawing employees' attention away from their work and onto the social gaffe episode, social gaffes could act as work interruptions that distract employees, resulting in low performance or poor quality of work (Puranik et al, 2020). It is also possible that trying to not think too much about the social gaffe and forcing oneself to focus on one's work is a depleting experience that results in lowered performance or job satisfaction (Leroy, 2009; Puranik et al, in press). We invite researchers to explore these possibilities to advance our knowledge of social gaffes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, by drawing employees' attention away from their work and onto the social gaffe episode, social gaffes could act as work interruptions that distract employees, resulting in low performance or poor quality of work (Puranik et al, 2020). It is also possible that trying to not think too much about the social gaffe and forcing oneself to focus on one's work is a depleting experience that results in lowered performance or job satisfaction (Leroy, 2009; Puranik et al, in press). We invite researchers to explore these possibilities to advance our knowledge of social gaffes.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited participants from a wide variety of organizations with the snowball sampling technique, that is the initial participants were invited from an MBA program, and then they recommended to others who might be interested in this study ( Puranik et al, 2021 ). The enrolled participants need to live with at least one family member, in order to have opportunity of displaying family role performance.…”
Section: Methodsmentioning
confidence: 99%
“…All survey items were self-reported, because we mainly focus on employees’ experience and subsequent response. Research also showed that when it comes to such state variables, it is acceptable for using the same-source data ( Puranik et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent ESM studies [45,46] recommend the minimum of three data points per person for statistically analyzing within-person, day-level relationships. In line with this recommendation, we included participants who completed at least 3 of the 10 daily surveys in our analysis by removing 5 respondents who contributed fewer than 3 complete daily data points.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…This approach allows for the simultaneous estimation of path coefficients for the hypothesized relationships considering the day-and person-level variances. Specifically, the effects of the within-person, day-level study variables (i.e., remote communication autonomy, positive affect, and proactive behaviors) and control variable (i.e., sleep quality) were modeled as random slopes at Level 1 [46,53]. The betweenperson moderator (i.e., techno-workload) and controls (i.e., job autonomy and demographic characteristics) were modeled as Level-2 constructs that exert cross-level effects on Level-1 variables and relationships.…”
Section: Analytic Approachmentioning
confidence: 99%